The Future of Eurozone Fiscal Governance - Anne-Laure Delatte; Clemens Fuest; Daniel Gros; Friedrich Heinemann; Martin Kocher; Roberto Tamborini (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2017)
This paper discusses various options for reforming fiscal governance in the Eurozone. We focus on two possible reform approaches referred to as the `Maastricht model' and the `US model'. The Maastricht model implies that ultimate responsibility for economic and fiscal policy remains at the national level. The US model, by contrast, calls for the development of much stronger European institutions. In both cases some degree of policy coordination, a European Banking Union and insolvency procedures for sovereigns are indispensable. We discuss the challenges and trade-offs involved and argue that certain elements of the two approaches which combine increased risk sharing with increased market discipline and risk reduction could be combined to achieve a more resilient and economically successful Eurozone.
Keywords: 330